2014
DOI: 10.3923/ajbs.2015.42.50
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Root-knot Nematodes (Meloidogyne spp.) Associated with Abelmoschus esculentus, Celosia argentea and Corchorus olitorius

Abstract: Vegetable crops are highly susceptible to a wide range of pests and diseases among which are the root-knot nematodes (Meloidogyne species). Traditionally, identification of Meloidogyne species had been based on use of morphological characters such as the perennial pattern. In recent times, accuracy of nematode identification using only morphological tools has been challenged due to similarities in morphological characters of some nematode species. The aim of this study was to identify the root-knot nematodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…The high inter and intra-specific variability in the Meloidogyne populations favors their adaptability and gives greater selective advantages over their hosts, being several Solanaceae species host of this nematode (González et al, 2010) how was observed in this study. Host-plant resistance to plant-parasitic nematodes is defined as the suppressive effect of the plant on the nematode's ability to reproduce (Cook and Evans, 1987). This definition of resistance in terms of reproduction of the nematode has been adopted by plant nematologists (Cook, 1974).…”
Section: Evaluation Of Wild Solanaceae Species Inoculated With M Incmentioning
confidence: 99%
See 1 more Smart Citation
“…The high inter and intra-specific variability in the Meloidogyne populations favors their adaptability and gives greater selective advantages over their hosts, being several Solanaceae species host of this nematode (González et al, 2010) how was observed in this study. Host-plant resistance to plant-parasitic nematodes is defined as the suppressive effect of the plant on the nematode's ability to reproduce (Cook and Evans, 1987). This definition of resistance in terms of reproduction of the nematode has been adopted by plant nematologists (Cook, 1974).…”
Section: Evaluation Of Wild Solanaceae Species Inoculated With M Incmentioning
confidence: 99%
“…There are more than 90 species of Meloidogyne identified, however M. arenaria, M. javanica, M. hapla and M. incognita are the most important because they cause major economic damage (De Jin et al, 2005;. Plants affected by nematodes showed symptomatology such as leaf yellowing, less growth and wilting and limited root development because of the formation of root knots, affecting the absorption of nutrients and decreasing yield (Daramola et al, 2015). Nematodes can interact with other diseases (i.e.…”
mentioning
confidence: 99%
“…Galls develop in the infected roots from the formation of giant cells used by this parasitoid as a source of nutrients. These modified cells can interfere with the flow of water and nutrients within plants, resulting in crop yield reductions or even the total loss of the crop (Daramola et al, 2015). Hussain et al (2011) found that an impaired development of okra was directly proportional to the initial nematode population density, yet inversely proportional to the age of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Reniforn nematodes causes severe damage to roots (Koenning et al, 1996). Daramola et al (2015) found relatively high populations associated with okra fields in the same state where the field experiments for this study were conducted. This implies that nemematode is probably widespread in parts of south western Nigeria and may go unnoticed as a pest of vegetable crops due to the apparent lack of root symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…R. reniformis is usually found in mixed populations with M. incognita and the disease symptoms in such situation is often only associated with root-knot nematodes. Many authors in Nigeria have found the reniform nematode in moderate populations associated with various crops (Adegbite et al, 2006;Olabiyi et al, 2009;Afolami et al, 2014;Daramola et al, 2015) but they did not consider the nematode to be damaging. This implies that the reniform nematode can be present in damaging populations and be left undiagnosed and uncontrolled due to lack of association as a potential pest problem.…”
Section: Discussionmentioning
confidence: 99%